A computerized method for loaded tooth contact analysis of high-contact-ratio spur gears with or without flank modification considering tip corner contact and shaft misalignment. (March 2016) - Ye, Siang-Yu; Tsai, Shyi-Jeng
Abstract: High-contact-ratio (HCR) spur gears have the advantages of reducing the acting loads on the teeth, as well as noise and vibration. However, the phenomenon of tip corner contact and the influence of shaft misalignments can cause unexpected damage and vibration. Flank modification is a solution for these influences. An efficient computerized tool for loaded tooth contact analysis (LTCA) is proposed in this paper that can be used to design HCR gears, while taking into consideration the conditions of tip corner contact and shaft misalignment. The LTCA method is developed based on the influence coefficient method and considers both the deformation of the loaded teeth and the twist deformation of the shaft. The variations of the shared loads and contact stress of a HCR spur gear pair with lead crowning and relieved profiles are analyzed considering the influence of the amount of shaft misalignment and relief. The contact patterns as well as the stress distribution on the engaged flanks in various cases are also simulated. Highlights: A LTCA approach for HCR spur gears considering the deformations of the teeth and the twist of the shaft is proposed. Two dimensional conditions of engaged flanks are involved in the LTCA model. The non-Hertzian contact on the tip corner and the face-end edge is analyzed and simulated. The influences of lead crowning and profile relief are studied. The loaded contact characteristics of various study cases are discussed systematically.